(untitled) (International Journal of Engineering and Computer Science, 2015)
Organizations are becoming more reliant than ever on data to run their business. But as the amount of data grows, policies and approaches for ensuring the safety and confidentiality of that information are falling behind. Companies need a more comprehensive approach to data privacy and protection, one that closes the gaps between business strategy, risk management, compliance reporting and IT security. A company’s approach to data protection and privacy should be more than legally compliant—it should be a core part of both the organization’s business value proposition and its culture. It should also be global in scope. All employees must understand this “culture of caring” and that they are accountable for safeguarding information. And as organizations innovate around new business models and technology to gain or maintain competitive edge, they must be equally aggressive in innovating around the data security issues that these advancements introduce. Therefore researchers have tried to draw the attention on how to prevent from data breaching in our nearby environment and to assist agencies and organizations to respond effectively to data breaches. [1]